IMPLEMENTATION OF GROUP GUIDANCE WITH GROUP DISCUSSION TECHNIQUES TO INCREASE LEARNING INTEREST OF STUDENTS SMAN 1 SUSUT - Made Wery Dartiningsih; Ni Luh Trisna Anggareni (Indonesian Journal of Educational Development (IJED), 2023)
This study aims to determine the application of group guidance using group discussion techniques to increase the learning interest of grade XII Language 3 students at SMAN 1 Susut in the academic year 2022/2023. This research includes Classroom Action Research, an effort carried out in a planned and systematic way by reflecting on service practices and then carrying out corrective actions to improve counseling service practices. The subjects of this study were students of class XII Language 3 SMAN 1 Susut who were selected for one class that showed a problem regarding low interest in learning, which was determined based on data from the guidance and counseling teacher as well as direct observation of the researcher, then through the interest in learning instrument it was found that five students became research subject. The results of this study indicate that group counseling services with group discussion techniques are very effective and can increase students' interest in learning by 73.8%. The researchers suggest counseling guidance teachers can use group guidance services with group discussion techniques as an appropriate alternative to address student problems, significantly increasing student interest in learning at SMAN 1 Susut.